2003
DOI: 10.1177/0193945903253092
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Reasoning in Experienced Nurses

Abstract: As an essential component of nursing practice, clinical reasoning is used to assimilate information, analyze data, and make decisions regarding patient care. Little is known about the reasoning strategies of experienced nurses who are not yet experts. This qualitative descriptive study explored the cognitive strategies used by experienced nurses as they considered assessment findings of assigned patients. To date, few studies of nurses' clinical reasoning have been conducted in a practice setting during actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
147
1
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(172 citation statements)
references
References 52 publications
12
147
1
8
Order By: Relevance
“…Thus, CJ included a series of phases of intellectual, psychological and practical behaviors. [10,11] Furthermore, congruent with the current study results, Simmons et al, 2003, explained that CJ in nursing necessitates a perception of the clinical situation, not related patient problems and illness, but about a holistic view of the patient experiences. Additionally, for resources, attitudes, & adaptations, CJ may be a difficult process for nurses.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Thus, CJ included a series of phases of intellectual, psychological and practical behaviors. [10,11] Furthermore, congruent with the current study results, Simmons et al, 2003, explained that CJ in nursing necessitates a perception of the clinical situation, not related patient problems and illness, but about a holistic view of the patient experiences. Additionally, for resources, attitudes, & adaptations, CJ may be a difficult process for nurses.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, for resources, attitudes, & adaptations, CJ may be a difficult process for nurses. [12] In contrary to the present result, much research has reported that the health care professionals have to comprehend the concept of CJ, essentially in the nursing field. Nurses should have unambiguous recognition of CJ components and phases, which afterward continuously and automatically represents clear interpretation.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Several studies identified the most frequent nursing diagnoses in different populations, but none in patients with liver cirrhosis [19][20][21][22] . In addition, few studies of clinical reasoning have been conducted in a practice setting 23 , and no studies focusing on clinical reasoning in patients with liver cirrhosis where published. The impetus of the study is to identify the priority focus of care for patients with a chronic condition using a clinical reasoning web, with the aims of reducing patients' length of stay, the risks associated with healthcare, and to improve patient's outcomes.…”
Section: The Casementioning
confidence: 99%